Sequencing and analysis of the complete mitochondrial genome of dog roundworm Toxocara canis (Nematoda: Toxocaridae) from USA. Issue 2 (3rd July 2019) - Meng, Xiaduo; Xie, Yue; Gu, Xiaobin; Zheng, Youle; Liu, Yunjian; Li, Yingxin; Wang, Lu; Zhou, Xuan; Zuo, Zhicai; Yang, Guangyou
Abstract: The dog roundworm Toxocara canis (Nematoda: Toxocaridae) is an important zoonotic parasitic nematode and cause toxocariasis in human with a worldwide distribution. Herein, the complete mitochondrial genome of a representative of this nematode from USA was determined through next generation sequencing platform. The whole genome was 14, 309 bp in size and encoded 12 protein-coding genes, 22 transfer RNAs, and 2 ribosomal RNAs. Phylogeny showed that although T. canis from USA and Australia were more closely related to each other than to that from Chinese, three T. canis isolates clustered together and formed paraphyletic relationships with T. cati and T. malayensis, supporting them as sister species among the family Toxocaridae. These cumulative mitochondrial DNA data should contribute to a better understanding of the phylogenetic relationship of this species.